The London Eye mystery - Dowd, Siobhan (New York : David Fickling Books, 2008)
When Ted and Kat's cousin Salim disappears from the London Eye ferris wheel, the two siblings must work together--Ted with his brain that is "wired differently" and impatient Kat--to try to solve the mystery of what happened to Salim.
"Originally published in Great Britain by David Fickling Books, an imprint of Random House Children's Books, in 2007"--T.p. verso.
Booklist starred.
Pub Weekly.
School Library Journal starred.
6.1
3-6
Keywords: Asperger's syndrome -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Cousins -- Juvenile fiction; Meteorology -- Juvenile fiction; Missing children -- Juvenile fiction; Asperger's syndrome -- Fiction; Brothers and sisters -- Fiction; Cousins -- Fiction; Meteorology -- Fiction; Missing children -- Fiction; Mystery and detective stories; Asperger's syndrome -- Fiction; Cousins -- Fiction; Meteorology -- Fiction; Missing children -- Fiction; Mystery fiction; Siblings -- Fiction; England -- Juvenile fiction; London (England) -- Juvenile fiction; England -- Fiction; London (England) -- Fiction; England -- Fiction; London (England) -- Fiction